PRODUKSI BIODIESEL DARI MINYAK KELAPA SAWIT DENGAN CO-SOLVENT FAME (FATTY ACID METHYL ESTERS) DAN APLIKASINYA PADA MOTOR BAKAR - Elvianto Dwi Daryono; Lalu Mustiadi (Jurnal Rekayasa Mesin, 2022)
The process of transesterification is slow due to the low solubility of triglycerides in methanol. The limitation of mass transfer can be overcome by adding a co-solvent. Co-solvent FAME is the right choice because it is the product of the reaction itself so that it does not require a separation process. The purpose of this study was to examine the use of FAME as a co-solvent in the transesterification of palm oil and its application to the combustion engine. The operating conditions were palm oil mass of 250 gr, NaOH catalyst 1.2% wt, stirring speed 100 rpm, reaction temperature 70oC, ratio molar of oil:methanol =1:6, reaction time (5,10,15,20,25,30 minutes), and co-solvent (0,5,10,15% wt). After the optimum conditions are obtained, the next step is to make biodiesel on a semi pilot plant scale. Oil, methanol, NaOH and co-solvent were put into a stirred reactor and heated at a reaction temperature of 70⁰C. After the reaction is complete then it is flowed into the separator for separation by adding hot water to form 2 layers. The top layer is biodiesel which was analyzed and performance test on the combustion engine. The optimum condition of the process is a reaction time of 10 minutes and the addition of 10% co-solvent, with a yield of 76.7783%. The results of the analysis of SNI 7182:2012 states that biodiesel meets almost all requirements. From the biodiesel performance test on the combustion engine, B10 got quite satisfactory results for the torque and opacity test parameters.